Surgical treatment outcomes and risk factors for post-TB lung disease - C. Guo; Q. Li; L. Wei; Y. Liu; D. Sun; C. Ding (IJTLD Open)
OBJECTIVE: This study aims to investigate the effectiveness and safety of surgical treatment for post-TB lung disease (PTLD) and to analyse its risk factors. METHODS: Data were collected from 268 patients who underwent pulmonary resection for TB in Xi’an Chest Hospital, Xi’an, Shaanxi, China, between January 2014 and December 2023. The efficacy and safety of the three groups were compared, and the TB group was used as the control group to analyse the risk factors of PTLD. RESULTS: The results indicated the three groups in intraoperative blood loss, post-operative drainage volume, post-operative complications, and post-operative hospital stay also varied significantly among the three groups (all P < 0.01). Additionally, factors such as pre-operative anti-TB therapy duration (OR = 1.02, P = 0.007), age (OR = 1.03, P = 0.030), and comorbid diabetes mellitus (OR = 3.00, P= 0.046) were identified as significant contributors to PTLD. While pre-operative haemoptysis demonstrates a statistically significant correlation with both precursor PTLDs, this association likely reflects the clinical expression of the underlying disease process. CONCLUSION: The study confirms that surgery for PTLD is safe and efficacious. Patients with advanced age, an extended duration of pre-operative anti-TB therapy, comorbid diabetes mellitus and pre-operative haemoptysis should maintain vigilance regarding the potential development of PTLD.